2014
DOI: 10.2215/cjn.12621213
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity, Age, and Risk of Hospital Admission and Length of Stay during the First Year of Maintenance Hemodialysis

Abstract: Background and objectives Although patients undergoing maintenance hemodialysis have exceptionally high hospitalization rates, the risk factors for hospitalizations are unclear. This study sought to examine hospitalization rates among hemodialysis patients in the United States according to both race/ethnicity and age.Design, setting, participants, & measurements US Renal Data System data on 563,281 patients beginning maintenance hemodialysis between 1995 and 2009 were analyzed. Rates of hospital admission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…This implicates that a greater number of people hospitalized in Najran do not have health insurance. This is parallel to the study of Yan et al, 13 where they found that patients without insurance have a higher risk for hospitalization. Table 2 represents the level of satisfaction of patients for all variables.…”
Section: Tools For Data Analysissupporting
confidence: 79%
“…This implicates that a greater number of people hospitalized in Najran do not have health insurance. This is parallel to the study of Yan et al, 13 where they found that patients without insurance have a higher risk for hospitalization. Table 2 represents the level of satisfaction of patients for all variables.…”
Section: Tools For Data Analysissupporting
confidence: 79%
“…The lower rate of receiving nephrologist care by the younger black patients with CKD, as described in this study, may be responsible, in part, for their poor outcomes reported in the literature (44)(45)(46)(47). Novel strategies aimed at improving pre-ESRD care for younger black patients and implemented both nationally and at the state level could have far-reaching effects.…”
Section: Discussionmentioning
confidence: 66%
“…Much more common in practice, though, are patients who present with prerenal azotemia or acute tubular necrosis due to various insults [36]. End-stage kidney disease patients are also at very high risk for hospitalization due to hypertensive urgency/emergency even after initiation of hemodialysis [37,38]. Post-acute management of patients with acute kidney injury focuses on avoidance of nephrotoxic medications including iodinated contrast, maintaining adequate urinary output with judicious use of diuretic medications, and control of BP [39].…”
Section: Common Inpatient Conditions Associated With Hypertensionmentioning
confidence: 99%